Pengelolaan Ekowisata dalam Perspektif Collaborative Governance untuk Mewujudkan Sustainable Tourism : (Studi Kasus: Uma Palak Lestari, Subak Sembung Peguyangan) - Ngakan Made Dwika Sutadewa; Komang Adi Sastra Wijaya; Ni Putu Anik Prabawati (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the management of ecotourism in Uma Palak Lestari, Subak Sembung Peguyangan, Denpasar City, from the perspective of collaborative governance to realize sustainable tourism. The research applies a descriptive qualitative approach. The data collection techniques used were observation, interviews, and documentation. The research findings show that the implementation of collaborative governance, involving local communities, government, traditional institutions, and CSR of Pertamina, significantly supports sustainable tourism. The collaboration encompasses participation, legitimacy, trust, accountability, and shared understanding. The process results in increased community empowerment, conservation of subak culture, and local economic development. However, challenges such as the lack of clear legal framework and limited promotion efforts are noted.